Global value chain participation and firms' innovations: Evidence from small and medium-sized enterprises in Viet Nam - Dang Duc Anh; Vuong Anh Dang (Asian Development Bank Institute (ADBI), 2020)
Participation in the global value chain could lead to different impacts on small and medium firms' performances. In this paper, we examine the relationship between the participation of the Vietnamese economy in the global value chain and small and medium firms' innovation in Viet Nam over the period 2007-2015. Using data from the Viet Nam Small and Medium Enterprise survey, we test whether a higher share of foreign value added in exports is likely to make small and medium firms innovate. To address the problem of omitted variable biases, we use the Chinese domestic value added in gross exports to the world as an instrument for foreign value added in gross exports in Viet Nam. We find that foreign value added in gross exports negatively correlates with firms' decision to introduce new products but positively associates with firms' decision to improve existing products. These relationships are more profound for firms in industrial zones and nonexporting firms. We also find evidence that the foreign value added in gross exports increases firm sales and have more subcontracts, which may help small and medium firms have more resources to innovate. As small and medium firms tend to improve existing products when they are more involved in global value chains, the government could use policies to incentivize small and medium firms to demand better technology, thereby improving the innovation system and creating a favorable environment in which to transfer new technology. These policy packages may include access to finance for those who invest in learning and adopt better technologies.
Keywords: F16; O24; 330; trade; small and medium-sized enterprises; global value chain; Viet Nam